AKHLAK MURID KEPADA GURU (KAJIAN CERAMAH BUYA YAHYA) - Nikmah, Akhodhatun (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2024)
Seeking knowledge is important for humans to survive in this world and the afterlife. Knowledge is like a light in the darkness, a guide for charity. On the other hand, there are things that really need to be paid attention to because no matter how high knowledge resides, it will not be good if manners and morals are marginalized. Therefore, through studying Buya Yahya's lectures, we find out about the key to gaining knowledge, on the al Bahjah TV YouTube channel entitled "The Morals of Students towards Teachers". This research uses a qualitative content analysis method. The author tries to analyze and understand the contents of the video as an object of research study. From Buya Yahya's narrative in his lecture, there are three keys to gaining knowledge, namely: 1) Mahabbah to the Teacher, 2) Being Civilized and Manners towards the Teacher, and 3) Serving the Teacher. It is important for students to pay attention to the teacher's morals. to be successful in seeking knowledge, and the knowledge gained is knowledge that is blessed and beneficial and is kept away from ulama' suu'.ABSTRAKMenuntut ilmu penting bagi manusia untuk keberlangsungan hidup di dunia dan akhirat. Ilmu bagaikan cahaya penerang di kegelapan, menjadi petunjuk bagi suatu amal. Di sisi lain ada hal yang sangat perlu diperhatikan karena setinggi-tingginya ilmu yang bersemayam, tidak akan memberikan kebaikan jika adab dan akhlak terpinggirkan. Maka dari itu melalui kajian ceramah buya Yahya kita mengorek tentang bagaimana kunci untuk mendapatkan ilmu, pada kanal youtube al Bahjah TV yang berjudul “Akhlak Murid kepada Guru”. Penelitian ini menggunakan metode analisis isi (content analysis) yang bersifat kualitatif. penulis berusaha untuk menganalisis dan memahami isi video tersebut sebagai obyek kajian penelitian. Dari penuturan buya Yahya dalam cermahnya ada tiga kunci untuk mendapatkan ilmu, yaitu: 1) Mahabbah Kepada Guru, 2) Beradab dan Bertata Krama kepada Guru, dan 3) Berkhidmat kepada Guru. Penting bagi murid untuk memperhatikan akhlak kepada guru. agar berhasil dalam menuntut ilmu, dan ilmu yang didapat adalah ilmu yang berkah dan manfaat serta dijauhkan dari ulama’ suu’.